Navigating cancer: Insights from patient journey mapping - Sarah Day; Jane Harries; Bukeka Sawula; Alec Payne; Shameem Bray; Denis Okova; Lauren Pretorius; Jennifer Moodley (PLoS ONE, 2026)
Background Cancer is an increasing public health problem in South Africa, with breast cancer being the most diagnosed cancer and cervical cancer the leading cause of cancer deaths among women. Despite the complexity of breast and cervical cancer patients’ journeys through the healthcare system, patients’ voices are still predominantly missing from the body of literature. Patient journey mapping, as a qualitative research method, offers an opportunity for centring patients in their care journeys and reimagine healthcare provision for the potential improvement of health systems and patient outcomes. Aim The aim of this study was to map journeys of breast and cervical cancer patients across the cancer care continuum. Methods Using patient journey mapping, we conducted six focus group discussions with patients with breast and cervical cancer who had completed treatment in Gauteng, KwaZulu Natal and the Western Cape, South Africa. The process involved three steps: 1.) development of individual maps; 2.) narrative sharing; and 3.) development of a collective map. Results of the study were shared in feedback sessions. Findings A total of 31 people participated in the focus groups: 23 with breast cancer, 7 cervical cancer and one had both cancers during her lifetime. The participants’ ages ranged between 30 and 69 years old. A patient journey map was developed drawing on the individual and collective maps and participant narratives. The findings of the paper constellate around three themes. The first theme, (de)personalised care, offers an examination of how relational, institutional and structural factors shape and are reshaped through participants lived experiences across the cancer care continuum. The second theme, self-advocacy, explores how participants advocate for their healthcare needs throughout the cancer care continuum. The third theme, intersecting vulnerabilities, explores how intersecting social identities, such as socioeconomic factors, gender, comorbidities and mental health, shape their cancer care journeys. Conclusions By centring patient with breast and cervical cancer voices, patient journey mapping not only showed where services and systems fall short but also provided guidance for redesigning a more patient responsive health system.